1995
DOI: 10.1038/ng1295-389
|View full text |Cite
|
Sign up to set email alerts
|

A mouse model of human familial hypocalciuric hypercalcemia and neonatal severe hyperparathyroidism

Abstract: Mice lacking the calcium-sensing receptor (Casr) were created to examine the receptor's role in calcium homeostasis and to elucidate the mechanism by which inherited human Casr gene defects cause diseases. Casr+/- mice, analogous to humans with familial hypocalciuric hypercalcemia, had benign and modest elevations of serum calcium, magnesium and parathyroid hormone levels as well as hypocalciuria. In contrast, Casr-/- mice, like humans with neonatal severe hyperparathyroidism, had markedly elevated serum calci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
416
2
2

Year Published

1997
1997
2010
2010

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 558 publications
(435 citation statements)
references
References 19 publications
15
416
2
2
Order By: Relevance
“…The derivation of the two parental strains of Casr À/À mice and 1a(OH)ase À/À mice by homologous recombination in embryonic stem cells was described previously by Ho and colleagues (4) and Panda and colleagues, (9) respectively. Briefly, a neomycin resistance gene was inserted into exon 5 of the mouse Casr gene.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The derivation of the two parental strains of Casr À/À mice and 1a(OH)ase À/À mice by homologous recombination in embryonic stem cells was described previously by Ho and colleagues (4) and Panda and colleagues, (9) respectively. Briefly, a neomycin resistance gene was inserted into exon 5 of the mouse Casr gene.…”
Section: Methodsmentioning
confidence: 99%
“…Western blot analysis of kidney membrane protein extract from homozygous Casr À/À mice confirmed that no detectable protein is expressed from this allele. (4) A neomycin resistance gene replaced exons VI, VII, and VIII of the mouse 1a(OH)ase gene (Cyp27b1), removing both the ligand-and hemebinding domains. Lack of 1a(OH)ase mRNA expression in kidney and of circulating concentrations of 1,25(OH) 2 D has been demonstrated previously.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations